Stressors in elite sport: A coach perspective - Thelwell, R. C.; Weston, N. J. V.; Greenlees, I. A.; Hutchings, N. V. (Journal of Sports Sciences, 2008)
We examined the varying performance and organizational stressors experienced by coaches who operate with elite athletes. Following interviews with eleven coaches, content analysis of the data revealed coaches to experience comparable numbers of performance and organizational stressors. Performance stressors were divided between their own performance and that of their athletes, while organizational stressors included environmental, leadership, personal, and team factors. The findings provide evidence that coaches experience a variety of stressors that adds weight to the argument that they should be labelled as "performers" in their own right. A variety of future research topics and applied issues are also discussed.